Evaluasi Kinerja Hot Well Pump Sebelum dan Setelah Perbaikan di PLTP PGE Kamojang Unit IV - Agustianawati, Shifa; Ignatius Riyadi Mardiyanto; Maridjo, Maridjo (SURYA TEKNIKA, 2024)
The Hot Well Pump plays a pivotal role in the primary cooling system of Geothermal Power Plants (PLTP). Issues arising with the Hot Well Pump can lead to a reduction in the generated electricity, emphasizing the critical importance of corrective maintenance. Pump performance serves as a crucial parameter in indicating the proper functioning of the pump. This study aims to analyze the impact of corrective maintenance on pump performance. The results demonstrate an increase in fluid flow rate from 3429.841 m³/h to 3746.420 m³/h, a decrease in pump head from 18.335 m to 17.463 m, an increase in hydraulic power from 167.244 kW to 172.992 kW, a decrease in input power from 369.162 kW to 332.531 kW, a decrease in shaft power from 345.167 kW to 319.121 kW, and an increase in efficiency from 48.407% to 54.721%. This performance improvement substantiates the effectiveness of corrective maintenance, including the replacement of riser pipe 1, upper shaft, O-ring, and shaft sleeve, in enhancing overall pump performance.